Place names and landscape character: a case study from Otago Region, New Zealand. (4th July 2017) - Atik, Meryem; Swaffield, Simon
Abstract: Landscape characterisation has become an important tool in the interpretation of the distinctive features, patterns and identity of a region for planning purposes. However, conventional assessment methods that focus upon visual character may overlook some cultural values. This study investigates how toponymy—the analysis of place names—can be undertaken as a contribution to landscape characterisation. The study focus is Otago Region, New Zealand, which has a diverse landscape and a reliable database of place names. The study reported here involves analysis of 696 place names relating to 31 types of landscape feature derived from maps. The majority of names were connected with symbolic historic and cultural associations, mainly people. Biophysical characteristics including landform and hydrological features were also prominent. Names associated with the indigenous culture, Maori, were layered with those from European colonisation. Systematic analysis of place names highlights both presence and displacements of cultural memory and offers potential for an additional rich layer of interpretation in landscape characterisation.